Rate Dynamics and Transmission Algorithms in Clustered Sensor Networks - Burrell, A.T.; Papantoni-Kazakos, P. (Discoveries in Agriculture and Food Sciences, 2014)
We consider wireless clustered sensor networks consisting of large numbers of life-limited sensors, where the size of each cluster is determined by the data rate generated by the sensors it contains. The limited sensors’ life-span and their possible mobility induce variations in the sensor population and data rate dynamics. The variations of the sensors’ population necessitate the deployment of random access data transmission algorithms, where stable such algorithms lie within the limited sensing class. We propose the deployment of the Limited Sensing Stack Random Access Algorithms (LSSRAAs), with a modification which allows the accommodation of high priority data. We evaluate the performance of the LSSRAAs in the presence of sensor expirations and recommend design specifications for systems with low versus relatively high energy reserves.